If a, b, c and d are distinct integers in arithmetic progression such that d = a 2 + b 2 + c 2 Then find a + b + c + d
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sorry, it should be 1 + 2 b − 6 b 2 is an integer.
Log in to reply
If x=2n where n is an integer, shouldn't x be even?
Log in to reply
Sorry, it should be 1 + 2 b − 6 b 2 is an odd integer for x to be an integer, because:
x = 2 1 ± 1 + 2 b − 6 b 2
Sorry guys, i don't have any appropriate solution from this problem. But maybe it can help this:
1st, Take a note that the series is in arithmetic progression so that means, if a is the first term then the second term must be a + d , 3rd is a + 2 d ) and and so on...
2nd, From the equation d = a 2 + b 2 + c 2 , the series must be a smaller integer because if the integer is larger, then it not might suitable to solve the equation.
3rd, By solving this, i assume that the middle b is zero. And it works. Possible solution is 2 = ( − 1 ) 2 + 0 2 + 1 2
Answer : − 1 + 0 + 1 + 2 = 2
SOMETIMES , we can solve the problem through our analysis by doing Assumption .
try it by hit and error method i considered the AP -1,0,+1,+2 and it satisfied the condition. so sum is 2
a = x − e
b = x
c = x + e
d = x + 2 e
We have equation to find the relationship between x and e:
x + 2 e = ( x − e ) 2 + x 2 + ( x + e ) 2
x + 2 e = 3 x 2 + 2 e 2
But since x, e are integers :
x < = 3 x 2 ( " = " < = > x = 0 )
2 e < = 2 e 2 ( " = " < = > ( e = 0 ) o r ( e = 1 ) )
but e must = 1 to make integers distinct.
So we only have (x,e) = (0,1) sum = 4x + 2e = 2.
first solve give equation d=a2 +b2+c2 a2+b2+c2-d=0 we know that 1 a2+1 b2+1 c2+(-1) d=0 we found coefficent of this equation is a=1,b=1,c=1,d=-1 we put this value in finding equation 1+1+1-1 =2 this is the answer
Problem Loading...
Note Loading...
Set Loading...
It happens again. I solve the problem but it shows that I did not.
Anyway, the solution is 2 by observation and then I calculated it as follows.
Since d = a 2 + b 2 + c 2 , this implies that d is the fourth term a 4 .
Let the first, second and third terms be a , b and c , then b − a = c − b = x , where x is the difference between two successive terms.
Then a = b − x , c = b + x and d = b + 2 x .
Therefore,
d = b + 2 x = ( b − x ) 2 + b 2 + ( b + x ) 2
⇒ b + 2 x = b 2 − 2 b x + x 2 + b 2 + b 2 + 2 b x + x 2
b + 2 x = 3 b 2 + 2 x 2
2 x 2 − 2 x + ( 3 b 2 − b ) = 0
⇒ x = 4 2 ± 4 − 8 ( 3 b 2 − b )
x = 4 2 ± 2 1 + 2 b − 2 4 b 2 )
Note that x = 2 n , when n is a positive integer.
For x = 2 n , implies that 1 + 2 b − 2 4 b 2 is an integer ⇒ b = 0 and x = 1 .
Therefore,
a = − 1 b = 0 c = 1 d = 2
⇒ a + b + c + d = − 1 + 0 + 1 + 2 = 2